Understanding Discontinuation Rates and Acceptance of the Low-Dose Levonorgestrel Intrauterine System in Spain: A Comprehensive Analysis of Bleeding Patterns and Influencing Factors - Josep Perelló-Capó; Gregorio López-González; María Isabel Lahoz-Pascual; Ana Isabel López-Castejón; Manuel Marcos-Fernández; Mercedes Andeyro-García; Ignacio Cristóbal-García; Joan Rius-Tarruella (Women's Health Reports)
Purpose: To estimate the 1-year continuation rate of low-dose levonorgestrel-releasing intrauterine systems (LNG-IUS) in Spanish women and elucidate potential factors impacting continuation. Materials and Methods: A prospective, multicenter, noninterventional study with a 1-year follow-up was conducted in Spain. Participants were 18–35-year-old women using low-dose LNG-IUS. Clinical and demographic data were collected, and the association between baseline characteristics and discontinuation rate was analyzed. Results: A total of 289 women (9.3% using 13.5 mg LNG-IUS and 90.6% using 19.5 mg LNG-IUS) completed the study, and 9% discontinued prematurely after 12 months. A statistically significant association was found between LNG-IUS discontinuation and educational level (odds ratio [OR] = 2.63; 95% confidence interval [CI]: 1.07–6.48), previous pregnancies (OR = 3.44; 95% CI: 1.40–8.46), and baseline intensity of menstrual pain (OR = 1.03; 95% CI: 1–1.04). In addition, both the change in the menstrual bleeding’s interference with daily life activities between the final and basal visit and the change in the pain associated with the intensity of menstrual bleeding showed a significant association with discontinuation. Conclusions: When recommending LNG-IUS, a patient’s baseline characteristics such as educational level, previous pregnancies, intensity of menstrual pain, and menstrual bleeding’s interference with daily life activities have to be considered. By doing so, health care providers can improve contraceptive counseling, reduce discontinuation rates, and enhance women’s satisfaction.